PESANTREN SEBAGAI PILIHAN UNTUK PENDIDIKAN:STUDI PILIHAN RASIONAL TERHADAP PARA ORANG TUA DI TANJUNGPINANG - Raudatul Awalia; Nanik Rahmawati; Rahma Syafitri (JURNAL SOSIO-KOMUNIKA, 2023)
Reports of sexual violence in Islamic boarding schools were widely heard at the end of 2021 where based on data from the National Commission on Women reported by Kompas.com, Islamic boarding schools were in second place after universities with cases of sexual violence, namely 19 percent. However, in reality not a few parents still choose to send their children to Islamic boarding schools, in the literature study it is stated that reporting which is part of media use can influence readers and listeners. This study aims to find out and describe the reasons why parents still choose to send their children to Islamic boarding schools amidst the widespread reporting of sexual violence in Islamic boarding schools. The method used in this research is a qualitative method with a descriptive approach. The theory used in this research is the Rational Choice Theory put forward by Jame S Coleman. Based on the results of the analysis it was found that the reason parents still send their children to Islamic boarding schools is because of the values ??contained in Islamic boarding schools, where Islamic boarding schools are believed to be a place for building character for children such as independence, responsibility, and discipline, then because of trust in Islamic boarding school managers, religious values, where the hours of religious learning in Islamic boarding schools are more than public schools or other Islamic-based schools so that children can be more intense in acquiring religious knowledge, and children are more minimized from negative associations that occur due to globalization